National approaches and solutions to the organization of the evacuation zone (exclusion) and the Polesie state radiation-ecological reserve in the post-chernobylperiod - Kudzin, Maksim V.; Kazakov, Aleksey S.; Pavlov, Dmitry E. (Journal of the Belarusian State University. Ecology, 2026)
The development of the Polesie State Radiation and Ecological Reserve is inextricably linked to the decision to establish an evacuation (exclusion) zone based on the updated radiation situation, determined by the exposure dose rate and the density of radioactive contamination from long-lived radionuclides of Chernobyl origin. This paper summarizes national legal experience in identifying and organizing specialized measures for the maintenance and management of the area most affected by the Chernobyl Nuclear Power Plant disaster. The stages of the post-Chernobyl period in the development of the area are identified based on the requirements of local regulations. A chronology of state management decisions is provided, taking into account the specific requirements for maintaining the area.
Keywords: evacuation zone (exclusion zone); radioactive contamination; concept; Polesie state radiation and ecological reserve